The Procedure For The Formation Of Strictly Agreed Prices In Construction (Eurasian Research Bulletin, 2022)
Without the rules and regulations of pricing and coordination, it will be difficult to establish optimal prices. In connection with the transition to free-market prices in a market economy in the construction industry, a number of difficulties arise in the formation of prices in comparison with other sectors of the economy.